Quantitative traits associated with seed yield and yield components in sunflower (Helianthus annuus L.): Quantitative traits associated with seed yield and yield components in sunflower (Helianthus annuus L.) - R SASIKALA; V SANTHIYA; S HARISH; M SENTHIVELU; T KALAIMAGAL (Journal of Oilseeds Research, 2023)
A total of 66 sunflower germplasm were planted in an augmented block design while adhering to all suggested best practices. According to correlation analyses, plant height, head diameter, and hundred seed weight were positively and significantly correlated with grain yield/plant. Oil content and volume weight were shown to be positively correlated. However, grain yield/plant and volume weight were found to be negatively correlated.